Histological study of quercus galls of Neuroterus quercusbaccarum (Linnaeus, 1758) (Hymenoptera: Cynipidae) - Kovácsné Koncz, Nóra (Acta Biologica Szegediensis, 2011)
The aim of this study is to reveal the histological structure of galls induced by Neuroterus quercusbaccarum and to identify accumulated secondary metabolism products and storage materials in gall tissue by histochemical methods. The galls induced by N. quercusbaccarum showed a concentrical layer tissue structure under light microsope. Directly next to the chamber, a protein and lipid containing nutritive tissue can be found, which is covered by sclerenchyma layer consisted of two large cell plates in the lenticular galls of the unisexual generation, while the bisexual generation induced grape shaped galls lack lignified sheaths. Our results confirm previous findings. The outer layer of the gall is the voluminous parenchymatic cortex with a supplying vascular network and covered epidermis. We proved with histological methods, that the galls really contain accumulated nutritives -proteins, lipids and starch- in large quantities. The concentration of these nutrients from the chamber toward the border of inner-gall, show a decreasing gradient in the case of proteins and lipids, and an increasing gradient for starch. We present the differences and similarities in histological structure among galls induced by two generations of N. quercusbaccarum and the well studied Biorrhiza pallida.